Assurer Reputation for Competence in a Multiservice Context* - Ganguly, Ananda R.; Herbold, Joshua; Peecher, Mark E. (Contemporary Accounting Research, 2007)
We experimentally examine determinants of the transferability and durability of an assurer's flagship-service reputation for competence in a multi-service context. Economic and psychology theories agree that transferability will increase when a new service and a flagship service require relatively similar, as opposed to relatively dissimilar, competencies. These theories disagree, however, regarding the durability of an assurer's flagship-service reputation following a performance failure in a new service. Economic theory requires some reciprocity for transferability and durability, and, accordingly, predicts that a new-service failure will inflict more damage on a flagship-service reputation when the new and flagship services require relatively similar, as opposed to relatively dissimilar, competencies. Psychology theory, in contrast, predicts that a new-service failure will tend not to damage the flagship-service reputation, even when the new and flagship services require relatively similar competencies. Thus, unlike economic theory, psychology theory predicts that relatively similar competencies between a new and a flagship service can improve the transferability of an assurer's flagship-service reputation for competence without reciprocally threatening its durability. Experimental findings indicate that reputation transferability increases when the new and flagship services require relatively similar, as opposed to relatively dissimilar, competencies. They also indicate that a new-service failure damages the flagship-service reputation only when, and to a greater degree when, the new and flagship services require relatively dissimilar, as opposed to relatively similar, competencies. Thus, empirically, greater similarity in the competencies required by a new and flagship service simultaneously enhances the transferability and durability of the assurer's flagship-service reputation. These empirical findings are better explained by psychology theory than by economic theory.